Fear Appeal as Coercion Versus Persuasion in a Democracy: The Power of Islamic Discourse in the Indonesian Public Sphere - Suwarno, Peter (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2019)
While Indonesia claims to be the world’s third largest democracy, it recognizes itself as both a secular and religious state. The negotiation of the state-religion relationship influenced by Islamic discourse continues to shape the socio-political development of this largest Muslim nation. This paper describes how Indonesia’s discursive contention is molded by the power and popularity of Islamic discourses. It will present examples and analysis of appeal to fear as coercive discourses from recently published speech events, debates, edicts, regulations, and publications as well as examine the vital role of Islamic discourses in the Indonesian public sphere and democracy. This paper concludes that coercive religious discourses and some government policies not only marginalize the voices of minority and opposing groups, but also curtail participative critical debates that are necessary for a democratic Indonesia.